RNA‐seq profiling of tubulointerstitial tissue reveals a potential therapeutic role of dual anti‐phosphatase 1 in glomerulonephritis. Issue 12 (29th April 2022) - Park, Sehoon; Lee, Hajeong; Lee, Jeongha; Lee, Sangmoon; Cho, Semin; Huh, Hyeok; Kim, Joo Young; Park, Minkyoung; Lee, Soojin; Kim, Yaerim; Choi, Murim; Joo, Kwon Wook; et al.
Abstract: Transcriptome profiling of tubulointerstitial tissue in glomerulonephritis may reveal a potential tubulointerstitial injury‐related biomarker. We profiled manually microdissected tubulointerstitial tissue from biopsy cores of 65 glomerulonephritis cases, including 43 patients with IgA nephropathy, 3 with diabetes mellitus nephropathy, 3 with focal segmental glomerulosclerosis, 3 with lupus nephritis, 4 with membranous nephropathy and 9 with minimal change disease, and additional 22 nephrectomy controls by RNA sequencing. A potential biomarker was selected based on the false discovery rate, and experiments were performed in TNF‐α‐stimulated primary cultured human tubular epithelial cells (hTECs). We identified 3037 genes with low expression and 2852 genes with high expression in the disease samples compared to the controls. Dual‐specificity phosphatase 1 (DUSP1) exhibited universal low expression in various diseases (log2 fold change, −3.87), with the lowest false discovery rate (7.03E‐132). In further experimental validation study, DUSP1 overexpression ameliorated inflammatory markers related to MAP kinase pathways in hTECs, while pharmacologic inhibition of DUSP1 increased these markers. The combination of DUSP1 overexpression with low‐concentration corticosteroid treatment resulted in more potent suppression of inflammation than high‐concentration corticosteroid treatment alone. The profiled transcriptomes provide insights into the pathophysiology of tubulointerstitial injury in kidney diseases and may reveal a potential therapeutic biomarker.